The war is here: considerations on brazilian poetry in times of crisis - de Oliveira, Vera Lúcia (2019)
Starting from the theme of the event, held by the Universidade Nova de Lisboa in October 2017, I outline a reflection on the trinomial "poetry, peace and war" based on the current Brazilian society, which rapidly loses some of the democratic achievements twenty years. How do Brazilian poets live this moment, how do they relate to it? To answer, I concentrated on a quick analysis of some poems by Donizete Galvão.